HUBUNGAN JENIS SUMBER AIR, KUALITAS BAKTERIOLOGIS AIR, PERSONAL HYGIENE DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS LAMPER TENGAH SEMARANG - Nurpauji, Siti Vitria; Nurjazuli, Nurjazuli; Hanani D., Yusniar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Diarrhea remains a public health problem in Indonesia. Based on health profile of Semarang City in 2012,IR (Incidence Rate) diarrhea 112 per 10.000 children under five years. From 37 public health center in the city of Semarang (2012), Public Health Center Lamper Tengah included public health center with IR highest diarrhea that amounted to 27 per 1000 children under five years. This research aimed to find out the association of type of water source, bacteriological qualityof water, andpersonalhygienewith the incidence ofdiarrheain children under five years in the working area of Public Health Center Lamper Tengah Semarang. The research using observational type with cross sectional design. The population in this study were children aged 12-59 months who visited taken Public Health Center at Lamper Tengah in October 2013-March 2014. Total samples were 83 respondents with proportional random sampling method. Analysis of the data used is chi-square test.The results of this research show the variables that are association with the incidence of diarrhea is type of drinking water source (p = 0,003), bacteriological quality of drinking water (p=0,001), mother habit of washing hands before feeding children(p=0,008), mother habit of washing hands after defecation (p=0,015), children habit of washing hands before eating (p=0,002), children habit of washing hands after defecation (p=0,005), maternal practices to manage food and beverage (p=0,001), and nail hygiene conditions of mother (p= 0,006). Whereas, variables of type of clean water sourceand nail hygiene conditions of children were not significant relate (p>0,05). From this research it was concluded that variables related to incidence of diarrhea children under five years in the working area of Public Health Center Lamper Tengah Semarang is type of drinking water source, bacteriological quality of drinking water, mother habit of washing hands before feeding children and after defecation, children habit of washing hands before eating and after defecation, maternal practices to manage food and beverage and nail hygiene conditions of mother.